Carpal Tunnel Syndrome as an Unusual Immune Checkpoint Inhibitor Adverse Effect: A Case Series and Review of the Literature - Shalata, Walid; Yakobson, Alexander; Massalha, Ismaell; Grinberg, Roxana D.; Goldstein, Iris M.; Gibbs, Rachel; Grinberg, Roy; Neime, Ala Eddin; Abu-Juma'a, Ali; Kian, Waleed; Peled, Nir; Rouvinov, Keren (International Journal of Innovative Research in Medical Science, 2020)
While immune checkpoint inhibitors (ICIs) have transformed standards of care and drastically improved patient prognoses in several malignant diseases, a range of immune related adverse events (irAEs) from ICIs have been observed. This case series describes the clinical course of three patients with unusual immune checkpoint-inhibitor (ICI) induced toxicities. These three patients developed carpal tunnel syndrome (CTS) while on ICI therapy. The first patient was a 79 year-old male who received neo-adjuvant chemo-immunotherapy and adjuvant immunotherapy (atezolizumab) for stage II-B lung adenocarcinoma, the second patient was a 70 year-old female who received immunotherapy only (nivolumab) for stage IV renal cell carcinoma and the third patient was a 71 year-old male who received adjuvant immunotherapy (nivolumab) for stage 2-A melanoma. The patients developed carpal tunnel syndrome with severe neuropathy as a result of therapy. All patients had complete symptomatic relief when treated with either corticosteroids or intravenous immunoglobulins for CTS.